2007
DOI: 10.1074/jbc.m703184200
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Aggrecan Loss from Aggrecan Proteolysis in ADAMTS-4 and ADAMTS-5 Single and Double Deficient Mice

Abstract: Aggrecan loss from mouse cartilage is predominantly because of ADAMTS-5 activity; however, the relative contribution of other proteolytic and nonproteolytic processes to this loss is not clear. This is the first study to compare aggrecan loss with aggrecan processing in mice with single and double deletions of ADAMTS-4 and -5 activity (⌬cat). Cartilage explants harvested from single and double ADAMTS-4 and -5 ⌬cat mice were cultured with or without interleukin (IL)-1␣ or retinoic acid and analyzed for (i) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Alternatively, glycosidases such as hyaluronidase could have more prominent roles in resorbing the aggrecan aggregate in growth cartilage (Durigova et al, 2007;Sztrolovics et al, 2002). The latter hypothesis is supported by data showing a lack of skeletal abnormality in ADAMTS-4-deficient mice (Glasson et al, 2004;Stanton et al, 2005), ADAMTS-5-deficient mice (Glasson et al, 2005;Stanton et al, 2005), ADAMTS-4/-5 doubledeficient mice (Ilic et al, 2007;Majumdar et al, 2007;Rogerson et al, 2008), and aggrecan knockin mice resistant to aggrecanase cleavage in the IGD . Aggrecan knockin mice resistant to MMP cleavage in the IGD are also skeletally normal .…”
Section: Adamts-5-deficient Mice Are Phenotypically Normalsupporting
confidence: 61%
See 2 more Smart Citations
“…Alternatively, glycosidases such as hyaluronidase could have more prominent roles in resorbing the aggrecan aggregate in growth cartilage (Durigova et al, 2007;Sztrolovics et al, 2002). The latter hypothesis is supported by data showing a lack of skeletal abnormality in ADAMTS-4-deficient mice (Glasson et al, 2004;Stanton et al, 2005), ADAMTS-5-deficient mice (Glasson et al, 2005;Stanton et al, 2005), ADAMTS-4/-5 doubledeficient mice (Ilic et al, 2007;Majumdar et al, 2007;Rogerson et al, 2008), and aggrecan knockin mice resistant to aggrecanase cleavage in the IGD . Aggrecan knockin mice resistant to MMP cleavage in the IGD are also skeletally normal .…”
Section: Adamts-5-deficient Mice Are Phenotypically Normalsupporting
confidence: 61%
“…Adenovirus infection of mouse synovium with connective tissue growth factor induces ADAMTS-5 expression and synovial fibrosis (Blaney Davidson et al, 2006). Galectin-3, a soluble lectin increased in human OA cartilage (Guevremont et al, 2004), weakly stimulates ADAMTS-5 expression in human OA chondrocytes (Janelle-Montcalm et al, 2007). Conversely, nutraceuticals such as glucosamine and chondroitin sulphate at biologically relevant concentrations decrease IL-1-induced ADAMTS-5 expression in bovine cartilage explants (Chan et al, 2006).…”
Section: Regulation Of Adamts-5 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggrecanase could pave the way for new therapeutic strategies, since it has been observed that ADAMTS-4 and ADAMTS-5 gene deletion decreases the severity of OA in animal models [77,78]. The TIMP-3 (tissue inhibitor of metalloproteinases-3) is the most important endogenous aggrecanase inhibitor identified so far [36,79].…”
Section: Pathogenesismentioning
confidence: 99%
“…All members of the ADAMTS proteoglycanases have been shown to, or are predicted to, cleave aggrecan however ADAMTS5 has emerged as the most important "aggrecanase" (pathologically), at least in the mouse, whereby catalytically inactivated Adamts5 (ΔCAT) homozygous allelic mice are protected from experimentally induced arthritis (Glasson et al, 2005;Stanton et al, 2005), which is not the case for Adamts1 and Adamts4 (Ilic et al, 2007) homozygous knockout mice. Most members of the ADAMTS proteoglycanases have also been shown to, or are predicted to, cleave versican (Sandy et al, 2001;Russell et al, 2003;Somerville et al, 2003;Westling et al, 2004;Silver et al, 2008;Longpre et al, 2009;McCulloch et al, 2009b) (Table 1) with ADAMTS5 showing the highest activity of all ADAMTS proteoglycanases characterised to date toward versican in vitro at the G1-DPEAAE cleavage site (pers.…”
mentioning
confidence: 98%